Synthesis of N-methylaniline by aniline alkylation with methanol over Sn-MFI molecular sieve - Niphadkar, P. S.; Joshi, P. N.; Gurav, H. R.; Deshpande, Suvarna S.; Bokade, Vijay V. (Catalysis Letters, 2009)
Sn-MFI molecular sieves (Tin silicalite-1) with SiO(2)/SnO(2) molar ratio of 50-150 were synthesized and characterized. Elemental analysis, XRD and DRUV-vis confirmed that prepared samples were of MFI zeolite structure and Sn was incorporated in MFI framework. Vapor phase methylation of aniline over Sn-MFI was systematically studied and optimizations of process parameters were carried out. Sn-MFI (SiO(2)/SnO(2) = 50) was found to be optimum catalyst with 55% aniline conversion and 60% N-methylaniline selectivity. At lower space velocity (higher contact time) of 1 h(-1), aniline conversion was found to be increased to 71% with reduction in N-methylaniline selectivity to 39% and increased in N,N-dimethylaniline selectivity to 58%. The reaction follows first order kinetics with respect to aniline having activation energy of 7.3 kcal/mol.
Keywords: Aniline; Lewis acid; Methanol; N-methylaniline; Sn-MFI

Tin-silicalite-1: synthesis by dry gel conversion, characterization and catalytic performance in phenol hydroxylation reaction - Niphadkar, Prashant S.; Kotwal, Mehejabeen S.; Deshpande, Shilpa S.; Bokade, Vijay V.; Joshi, Praphulla N. (Materials Chemistry and Physics, 2009)
Tin-silicalite-1 (Sn-MFI) has been successfully synthesized by dry gel conversion (DGC) method. The influence of various synthesis parameters such as crystallization time, temperature, water content at the bottom of autoclave, molar ratios of (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) in dry gel on the crystallization kinetics and physico-chemical properties of Sn-MFI materials has been investigated. Powder-X-ray diffraction (XRD),XPS,AAS, DRUV-vis and SEM techniques were employed as characterization tools. Time-dependent studies revealed that, the progressive crystallization of Sn-MFI depend not only on the synthesis time but also on the other various synthesis parameters. Increase in the crystallization temperature, water content at bottom of autoclave (TPA)(2)O/SiO(2) and SiO(2)/SnO(2) molar ratios in dry gel resulted in the lowering of overall crystallization period. A good correspondence between the chemical composition of the surface and the bulk indicated the uniform distribution of Sn(4+) ions. The presence of these ions in tetrahedral coordination has been indicated by DRUV-vis spectral studies. Although, not better but comparable activity has been shown by Sn-MFI prepared by dry gel conversion method with Sn-MFI prepared by conventional hydrothermal crystallization method in the hydroxylation of phenol reaction. Increase in concentration of isolated Sn(4+) ions led to increase in phenol conversion and H(2)O(2) efficiency. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: crystallisation; Dry gel conversion; microporous materials; Sn-MFI

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Characterization of surface acid sites in tin-silicalite-1 (Sn-MFI) molecular sieve by X-ray photoelectron spectroscopy - Niphadkar, P. S.; Patil, K. R.; Joshi, P. N. (Microporous and Mesoporous Materials, 2011)
The nature, strength and density of surface acid sites in Sn-MFI molecular sieves with different Sn-content were characterized by N 1s high resolution photoelectron peak of chemisorbed pyridine in combination with pyridine-IR and TPAD. Two peaks emerged at 399.5 +/- 0.2 and 401.5 +/- 0.2 eV by deconvoluting composite N is peak were assigned to chemisorbed pyridine on weak and relatively strong Lewis acid sites, respectively. The relative percentage of strong Lewis acid sites was found to increase with the decrease of framework Sn content. A close agreement was observed between the ratios of weak Lewis acid sites to strong Lewis acid sites obtained from XPS and TPAD. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: Lewis acidity; Pyridine chemisorption; SiO2/SnO2 molar ratio; Sn-MFI; XPS

Crystallization kinetics of Sn-MFI molecular sieve formation by dry gel cross mark conversion method - Niphadkar, P. S.; Tangale, N. P.; Joshi, P. N.; Awate, S. V. (Microporous and Mesoporous Materials, 2013)
The conversion of amorphous stannosilicate dry gel into crystalline molecular sieve with MFI structure (Sn-MFI) was achieved by dry gel conversion (DGC) method at 413, 443 and 473 K. For comparison purpose, Sn-MFI molecular sieve with similar SiO2/SnO2 mole ratio was also obtained by hydrothermal crystallization route. Crystallization curves were established by conducting time dependant studies on progressive crystallization processes for both the systems. The values of activation energy of nucleation (E-n), activation energy of crystallization (E-c), and their pre-exponential factors (InA(n), InA(c) respectively) were calculated from Arrhenius plots. Compared to the hydrothermal method, shorter induction period was observed when DGC method was employed. Both the E-n (49.70 kJ/mol) and E-c (52.82 kJ/mol) for DGC method were found to be lower than that of the E-n (55.70 kJ/mop and E-c (60.23 kJ/mol) for hydrothermal method. The kinetics parameters viz. K and q were derived from kinetic expressions and DGC method showed higher value of K and lower value of q compared to hydrothermal crystallization method at identical temperature. Various DGC method parameters such as water content at the bottom of autoclave and SiO2/SnO2 mole ratio have shown the influence on the kinetics of crystallization of Sn-MFI. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Crystallization; DGC; kinetics; Nucleation; Sn-MFI